ANALISIS KESALAHAN SISWA MTs TERHADAP KONSEP PERSAMAAN LINEAR SATU VARIABEL - Rika Sapitri; Wahyu Setiawan; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to analyze the errors of MTs students on the concept of a one-variable linear equation (PLSV), using a qualitative descriptive research method. The data collection in this study was carried out by providing 7 questions about the concept of a one-variable linear equation (PLSV) and interviews with the data processing technique used, namely analyzing student errors, based on indicators of error in understanding the definition of a one-variable linear equation. The subject that the researcher used was 19 students of class VII-B in one of the private MTs in Cipeundeuy District with heterogeneous abilities. From the results of the study stated that; (1) the type of error students with low ability make is wrong when determining which incluades a one-variable linear equation, not a one-variable linear equation and cannot mention the variables and constants of an equation; (2) the type of error made to the medium ability student cannot mention the constant of an equation; and (3) the type of error of students with high ability is wrong in mentioning constants. So it can be concluded that the cause of student errors is that there are still many who do not understand the basic concept of a one-variable linear equation.